STRATEGI MANAJEMEN PEMASARAN PENDIDIKAN DALAM MENINGKATKAN KEPUASAN PELAYANAN ADMISITRASI : STUDI KUALITATIF DI SMA NEGERI 1 DRAMAGA BOGOR - Mukhlis, Muhammad; Sarifudin; Ade Qohar (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines education marketing management strategies based on hybrid 7P marketing mix to enhance administrative service satisfaction at SMA Negeri 1 Dramaga Bogor. The main problem is how public schools with regulatory and budget constraints achieve 93% satisfaction with zero complaints. Research objectives identify 7P implementation (Product-Place-Promotion-People-Process-Physical Evidence-Price) and analyze hybrid digital-humanistic model contribution. Qualitative case study method employed in-depth interviews (30 points) with Quality Control and Administration Heads, 15-hour participatory observation, and document analysis. Findings reveal Jibas-SPMB (Product) 98.3% accuracy, full WiFi coverage-strategic layout (Place) 97.1% IKM, IG/TikTok-Web (Promotion), 72-hour annual staff training (People), and WA HUMAS <2-hour Six Sigma 3.4 (Process).